Growth factor gradient bionic scaffold and application thereof in tendon-bone interface repair
Core-shell nanofiber structures were prepared by coaxial electrospinning and self-assembly techniques, which solved the problem of growth factor gradient distribution and release, realized integrated repair of tendon-bone interface, and promoted tendon-bone tissue regeneration.
Patent Information
- Application Number
- CN202511438220.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-10
- Publication Date
- 2026-02-03
AI Technical Summary
Existing technologies struggle to achieve gradient distribution and programmed controlled release of growth factors, resulting in poor tendon-bone interface repair. Furthermore, traditional preparation methods cannot maintain the biological activity of growth factors.
Core-shell nanofiber structures were prepared using coaxial electrospinning and self-assembly techniques. BMP-2-loaded microspheres were then prepared by ultrasonic emulsification and combined with a polydopamine coating to achieve the sequential release of various growth factors, mimicking the gradient structure of the tendon-bone interface and promoting the hierarchical differentiation of mesenchymal stem cells.
It achieves gradient programmed release of multiple growth factors, and synergistically induces integrated repair of the tendon-bone interface through scaffold structure, thereby improving the regeneration effect of tendon-bone interface tissue and maintaining the bioactivity and release rate of growth factors.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
TECHNICAL FIELD
[0001] The application prepares a gradient biomimetic scaffold capable of releasing multiple growth factors in sequence, which can synergistically promote tissue regeneration, and belongs to the technical field of tissue repair material preparation. Specifically, a new method for constructing a multiple growth factor sequential release system is adopted by using coaxial electrospinning technology and self-assembly technology, which can realize the sequential controllable release of multiple growth factors in core-shell nanofibers. BACKGROUND
[0002] The tendon-bone interface is a heterogeneous tissue, which has significant hierarchical characteristics in structural composition, cell type, extracellular matrix and mechanical properties, and has limited self-repairing ability. The gradient tissue cannot be regenerated synchronously, and the healing interface is mostly scar tissue, which cannot effectively transmit stress and maintain the stability of the interface. Therefore, the integration reconstruction of the heterogeneous tissue structure of the tendon-bone interface is the key to the repair of tendon-bone injury, and is also a research hotspot and difficulty in the field of sports medicine. Although the existing tissue engineering technology can simulate the gradient structure of the tendon-bone interface through the scaffold, and regulate the differentiation of mesenchymal stem cells and the deposition of extracellular matrix, a single scaffold cannot meet the gradient repair requirements. Growth factors (such as BMP-2, TGF-β1, CTGF) can induce cell directional differentiation, but the traditional delivery system cannot realize the gradient distribution and programmed release of growth factors, and is easy to cause the loss of activity of growth factors, which is difficult to realize the efficient repair of the tendon-bone interface with the scaffold. Therefore, it is of important clinical significance to develop a material that can realize the gradient release of growth factors and the integration repair of the tendon-bone interface induced by the scaffold structure. Growth factors are a class of natural biological media that regulate key cell activities in the process of tissue repair and regeneration, which promote tissue regeneration and healing by inducing cell growth and proliferation. In the process of tissue formation, development and repair, various growth factors act at different stages, and there is mutual coordination. However, the regulation of growth factors on tissue regeneration is affected by many factors, including the combination, dosage, carrier and release rate of growth factors. Therefore, it is necessary to construct a carrier system with sequential release characteristics of multiple growth factors according to the induction characteristics and mechanism of different factors, so as to simulate the physiological process of tissue regeneration and release different growth factors to the required tissue and cells in time and appropriate amount.
[0003] There are many methods to prepare tissue engineering scaffolds, mainly including fiber connection method, solvent casting / particulate leaching method, thermally induced phase separation method, electrospinning method, freeze-drying method, in-situ polymerization method, etc. These methods need to use a large amount of organic solvent and need to be carried out under harsh conditions such as high temperature, and the preparation process is complex, and the integrity of the biological activity of the protein growth factor cannot be maintained. The electrospinning method is considered to be one of the most effective methods for preparing nanofiber materials. The tissue engineering fiber scaffold prepared by this method has good pore connectivity and is similar to the natural extracellular matrix, which is beneficial to the adhesion, proliferation and differentiation of cells. As a breakthrough of electrospinning technology, the coaxial electrospinning can load bioactive factors in the core layer material, and maximize the activity of the growth factor. The combination of coaxial electrospinning technology and electrostatic layer-by-layer self-assembly technology can realize the step-by-step release of multiple growth factors, so as to meet the needs of different growth factors at different stages of tissue regeneration and repair. SUMMARY
[0004] The purpose of the present application is to provide a preparation method of a growth factor gradient biomimetic scaffold, which can realize the gradient programmatic release of multiple growth factors, simulate the gradient structure of the tendon-bone interface, induce the hierarchical differentiation of mesenchymal stem cells, and promote the integrated repair of the gradient structure of the tendon-bone interface. The process steps adopted by the gradient controlled release scaffold prepared by the present application for step-by-step release of multiple growth factors are as follows: (1) Using ultrasonic emulsification method to prepare BMP-2 loaded polylactic acid microspheres; (2) Dissolving PCL in a mixed solution of chloroform and methanol as a shell solution; (3) Dissolving PVA in deionized water, after fully dissolving, adding TGF-β1 growth factor and mixing evenly as a core layer solution; (4) The core layer and shell layer solutions are respectively filled into different syringes, and a core-shell directional fiber membrane loaded with growth factors in the core layer is prepared by using coaxial electrospinning technology. Freeze-drying to remove residual solvent.
[0005] (5) Loading CTGF to the outer surface of the core-shell fiber membrane by polydopamine coating, and freeze-drying to obtain a core-shell directional nanofiber membrane which releases multiple growth factors at different rates in sequence.
[0006] (6) Dissolving PCL in a mixed solution of chloroform and methanol, uniformly dispersing the BMP-2 loaded polylactic acid microspheres and nano-hydroxyapatite (nHAp) into the gelatin solution. Non-directional nanofiber layer is obtained by co-electrospinning, vacuum drying and removing residual solvent.
[0007] (7) Adding gelatin solution between the prepared core-shell directional fiber layer and non-directional nanofiber layer to bond them together and freeze-dry for storage.
[0008] In step 1, the BMP-2-loaded polylactic acid microspheres are prepared by ultrasonic emulsification. PLLA and PEG are dissolved in dichloromethane to form an organic phase, and the BMP-2 solution is added under ice bath and ultrasonic emulsified for 5 min to form an O / W type primary emulsion, and then 1% PVA is added and ultrasonic emulsified for 10 min to form a W / O / W type multiple emulsion. The solvent is volatilized under room temperature and 500 rpm magnetic stirring for 4 h, and then the microspheres are washed with deionized water and freeze-dried, and stored at-20℃.
[0009] In step 1, the average particle size of the BMP-2-loaded polylactic acid microspheres is 0.6726±0.2343μm, and the microspheres are spherical and non-adherent. The particle size is beneficial to the uniform dispersion of the microspheres in the non-oriented fiber layer, and facilitates the slow release of BMP-2.
[0010] In step 2, the shell material is a synthetic polymer material, such as polylactic acid, lactic acid-glycolic acid copolymer, polycaprolactone, etc., with a molecular weight of 100-300 million and a mass concentration of 5-20 %(w / v). The solvent is a mixture of one or more of dichloromethane, trichloromethane, trifluoroethanol, hexafluoroisopropanol, and methanol.
[0011] In step 3, the growth factor added to the core layer solution is one or more, such as bone morphogenetic protein (BMP), fibroblast growth factor (FGF), vascular endothelial cell growth factor (VEGF), etc., or a polypeptide or other biologically active substance, with a mass concentration of 10-20 μg / mL.
[0012] In step 4, the coaxial electrospinning technology is used to prepare the core-shell fiber, and the process parameters are as follows: temperature 20-30℃, relative humidity 35-45%, core spinning solution flow rate 0.0005-0.001 mm / s, shell spinning solution flow rate 0.0025-0.003 mm / s, negative voltage 15-20 kV, receiving distance 10-20 cm. The temperature for vacuum drying is 30-37℃, and the time is 24-48 h.
[0013] In the step 5, when the fiber scaffold is loaded with the growth factor by using the polydopamine, the polydopamine coating can not only realize the stable loading of CTGF, but also improve the biocompatibility of the fiber surface and promote cell adhesion. The obtained core-shell directional nanofiber is vacuum dried for 24 h, then immersed in a PDA solution (4 mg / ml, 10 mM Tris HCl, pH 8.5) and shaken on a shaking table at room temperature for 24 h; then washed with deionized water for 3 times to remove the unattached PDA; after freeze-drying, the sterilized scaffold is immersed in a growth factor solution, the amount of growth factor is 10-20 μg / mL, and the solvent is water, PBS buffer, etc. At room temperature, the scaffold is continuously shaken on a shaking table for 24 h (100 rpm) to fully load the growth factor; finally, the core-shell directional nanofiber scaffold loaded with the growth factor is obtained by freeze-drying.
[0014] In the step 6, the spinning material is one of natural polymer materials such as gelatin, chitosan, hyaluronic acid, polyethylene glycol, collagen, etc., and one of synthetic polymer materials such as polycaprolactone, poly-lactide, poly(lactic-co-glycolic acid), etc., the mass concentration is 10-20 %(w / v), the solvent is one or more of dichloromethane, trichloromethane, trifluoroethanol, hexafluoroisopropanol, methanol, etc., the volume ratio of the mixed solvent is 1:3-3:1, and the amount of the growth factor-loaded polylactic acid microspheres and nanohydroxyapatite is 100-200 and 30-50 μg / mL, respectively.
[0015] In the step 6, the non-directional fiber is prepared by using the co-electrospinning technology, and the process parameters are as follows: temperature 20-30℃, relative humidity 35-45%, the flow rate of the polycaprolactone and gelatin solution is controlled to be 0.002 mm / s and 0.0015 mm / s, respectively, negative voltage 15-20 kV, and receiving distance 10-20 cm. The temperature of vacuum drying is 30-37℃, and the time is 24-48 h.
[0016] In the step 7, the gelatin adhesive is a 1.0% gelatin aqueous solution prepared by dissolving gelatin in a 37℃ water bath.
[0017] The application realizes preparation of a gradient biomimetic scaffold capable of releasing multiple growth factors in stages by nuclear shell structure design and fiber orientation difference, so as to synergistically promote regeneration and repair of the tendon-bone interface. First, the nuclear shell structure nanofiber is prepared by using coaxial electrospinning technology, and different growth factors are loaded into the core and shell structures of the fiber. The nuclear shell fiber not only can simulate the natural extracellular matrix, but also can effectively ensure the biological activity and release rate of the growth factors loaded in the core. Second, the growth factors loaded by polydopamine have unique advantages, which can effectively control the total amount of cytokines loaded on the outer surface of the fiber membrane, have good biocompatibility and biodegradability, and can effectively maintain the activity of the growth factors. In addition, the directional fiber layer simulates the tendon structure, and the non-directional fiber layer (containing nano-hydroxyapatite) simulates the bone tissue, forming a gradient structure, and synergistically inducing mesenchymal stem cells to differentiate. In summary, the integrated scaffold with gradient structure and hierarchical induction function prepared by the application provides a“regional”microenvironment for heterogeneous tissue regeneration through the synergistic effect and programmed release of growth factors and the orientation structure of fibers, and realizes the integrated repair of the tendon-bone interface.
[0018] The composite scaffold obtained by the method has great promoting effect and application prospect in the field of protein macromolecular drug delivery carriers and regenerative medicine. BRIEF DESCRIPTION OF DRAWINGS
[0019] Figure 1 Scanning electron microscope image of the polylactic acid microspheres loaded with bone morphogenetic protein 2 prepared in embodiment one of the application Figure 2 Scanning electron microscope image of the polylactic acid microspheres loaded with bone morphogenetic protein 2 prepared in embodiment one of the application Figure 3 Laser confocal image of the polylactic acid microspheres loaded with bone morphogenetic protein 2 prepared in embodiment one of the application Figure 4 Scanning electron microscope image of the polylactic acid microspheres loaded with bone morphogenetic protein 2 prepared in embodiment one of the application Figure 5 Scanning electron microscope image of the polylactic acid microspheres loaded with bone morphogenetic protein 2 prepared in embodiment one of the application Figure 6 Transmission electron microscope image of the non-directional electrospinning loaded with nano-hydroxyapatite and bone morphogenetic protein 2 nanomicrospheres in embodiment one of the application Figure 7 Laser confocal image of the composite scaffold showing the layered structure in three-dimensional space in embodiment one of the application The application will be further described in detail below in conjunction with the accompanying drawings and the following examples, but the application should not be limited by the content. Simple improvements to the method of the application under the concept of the application are within the scope of the application.
[0020] Example 1
[0021] Take 250 mg PLLA and PEG to dissolve in 5 mL dichloromethane to form an organic phase, after complete dissolution, slowly add 250 μL of 50 μg / mL BMP-2 solution under ice bath conditions, move it to the amplitude bar of the ultrasonic cell crusher, ultrasonic emulsification for 5 minutes, form O / W type primary emulsion. Add 10 mL of 1% PVA, ultrasonic emulsification for 10 minutes, form W / O / W type multiple emulsion. Under room temperature and normal pressure, magnetic stirring at 500 rpm for 4 hours, make the dichloromethane solvent completely volatilize, and the emulsion droplets solidify into microspheres, transfer the remaining solution to a centrifuge tube, balance, freeze the centrifuge at 4℃ 5000 rpm for 10 minutes, discard the supernatant, resuspend and wash with appropriate amount of deionized water, and wash away the excess PVA aqueous solution and free drugs. After centrifugation, the precipitate is freeze-dried and transferred to a dryer for storage in a -20℃ refrigerator. Scanning electron microscope is used to observe the morphology of the microspheres, as shown in FIG. 1. Figure 1
[0022] Step 2 Preparation of core-shell nanofiber membrane loaded with transforming growth factor (TGF-β1) Dissolve 0.6g PCL in 4mL trifluoroethanol and methanol mixed solvent, the volume ratio of trifluoroethanol and methanol is 3:1, magnetic stir overnight to make it fully dissolved, get a uniform shell solution with a mass fraction of 15%, use a syringe to deliver to the outer coaxial needle, in addition, take PVA 0.48g dissolved in 4mL deionized water, use 95℃ water bath stirring to make it fully dissolved, get a uniform spinning solution with a mass fraction of 12% for standby, before starting electrospinning, dissolve TGF-β1 in the above spinning solution to get a core spinning solution containing 10 μg / mL TGF-β1, use another syringe to deliver the gelatin spinning solution to the inner coaxial needle, adjust the electrospinning process parameters, electrospin at a voltage of 20 kV with a push speed of core 0.0004 mm / s and shell 0.002 mm / s, adjust the receiving distance to 15 cm, control the temperature at 25℃ and the humidity at 45%, complete the preparation of nanofiber membrane, place the prepared fiber membrane in a vacuum drying oven at 37℃ for 48h to remove the residual solvent, standby. Scanning electron microscope is used to observe the morphology of the core-shell fiber, as shown in FIG. 2. Figure 2
[0023] The prepared PCL-PVA membrane was thoroughly washed with deionized water and set aside. A 4 mg / mL polydopamine (PDA) solution (10 mM Tris HCl, pH=8.5) and a 100 μg / mL aFGF solution were prepared. The PCL-PVA membrane was then immersed in the PDA solution and shaken on a shaker at room temperature for 24 h. It was then rinsed three times with deionized water for 10–30 s each time (this operation was performed at 4 °C). Finally, it was lyophilized to obtain the PDA-loaded PCL-PVA scaffold. This scaffold was then immersed in a 200 μg / mL CTGF solution and shaken continuously at 100 rpm for 24 h at room temperature to ensure sufficient CTGF loading. Finally, it was lyophilized to obtain CTGF-loaded core-shell fibers. The morphology of the self-assembled fibers was observed using scanning electron microscopy, as shown in the attached figure. Figure 3 As shown in the attached image. Laser confocal microscopy was used to observe the structure of core-shell fibers. Figure 4 As shown.
[0024] PCL was dissolved in a mixed solution of chloroform and methanol (volume ratio 5:1). BMP-2 polylactic acid microspheres and nano-hydroxyapatite (nHAp) were added to a gelatin solution of 2,2,2-trifluoroethanol to obtain spinning solutions of 20% and 10%, respectively. The two solutions were electrospun together using two 10mL syringes at flow rates of 0.002mm / s and 0.0015mm / s, respectively. All electrospinning processes were carried out at 25°C and 45% humidity. Finally, the obtained non-oriented nanofibers were vacuum dried for two days for later use.
[0025] Weigh a certain amount of gelatin, place it in a 37 ℃ water bath and add water to dissolve it, prepare a gelatin aqueous solution with a mass concentration of 1.0% as an adhesive, drop the gelatin solution between the prepared oriented fiber layer and the non-oriented fiber layer to bond them together, freeze dry and store for later use.
Claims
1. A gradient biomimetic scaffold capable of sequentially releasing multiple growth factors, characterized in that, The method includes the following steps: (1) Polylactic acid microspheres loaded with BMP-2 were prepared by ultrasonic emulsification; (2) Dissolve PCL in a mixed solution of chloroform and methanol to form a shell solution; (3) Dissolve PVA in H2O. After it is fully dissolved, add TGF-β1 growth factor, mix well, and use it as the core layer solution. (4) The core and shell solutions were loaded into different syringes, and a core-shell oriented fiber membrane loaded with growth factors was prepared by coaxial electrospinning. The membrane was then freeze-dried to remove residual solvent. (5) CTGF was loaded onto the outer surface of the core-shell fiber membrane by polydopamine coating and freeze-dried to obtain a core-shell oriented nanofiber membrane that releases multiple growth factors at different rates. (6) Dissolve PCL in a mixed solution of chloroform and methanol, and uniformly disperse BMP-2-loaded polylactic acid microspheres and nano-hydroxyapatite (nHAp) in the gelatin solution. Obtain a non-oriented nanofiber layer by co-electrospinning, and vacuum dry to remove residual solvent; (7) Add the gelatin solution dropwise between the prepared core-shell oriented fiber layer and the non-oriented nanofiber layer to bond them together. Then freeze-dry and store for later use.
2. The growth factor gradient biomimetic scaffold according to claim 1, characterized in that, The BMP-2-loaded polylactic acid microspheres were prepared by the following method: PLLA and PEG were dissolved in dichloromethane to form an organic phase. BMP-2 solution was added under ice bath and ultrasonically emulsified for 5 min to form an O / W type primary emulsion. Then, 1% PVA was added and ultrasonically emulsified for 10 min to form a W / O / W type secondary emulsion. The mixture was magnetically stirred at 500 rpm for 4 h at room temperature to evaporate the solvent. The mixture was then centrifuged at 4℃ and 5000 rpm for 10 min. After washing with deionized water, the mixture was freeze-dried and stored at -20℃.
3. The growth factor gradient biomimetic scaffold according to claim 1, characterized in that, The polylactic acid microspheres loaded with BMP-2 have an average particle size of 0.6726±0.2343μm and are spherical and non-adhesive.
4. The growth factor gradient biomimetic scaffold according to claim 1, characterized in that, The core-shell oriented nanofibers are prepared by the following method: PCL is dissolved in a mixture of chloroform and methanol as the shell liquid, and TGF-β1 is added to a PVA aqueous solution as the core liquid; Shell liquid and core liquid were delivered separately through outer and inner coaxial needles, with a core liquid flow rate of 0.0004 mm / s and a shell liquid flow rate of 0.002 mm / s. A DC voltage of 20 kV was applied, and the spinning distance was 15 cm. Electrospinning was carried out at 25°C and 60% humidity. The resulting nanofibers were freeze-dried for 24 h and then immersed in 4 mg / ml PDA solution (10 mM Tris-HCl, pH 8.5), shaken on a shaker at room temperature for 24 h, rinsed three times with deionized water, freeze-dried, and then immersed in CTGF solution, shaken on a shaker at 100 rpm at room temperature for 24 h, and then freeze-dried to obtain the final product.
5. The growth factor gradient biomimetic scaffold according to claim 1, characterized in that, The non-directional nanofibers were prepared by the following method: PCL was dissolved in a mixed solution of chloroform and methanol, and BMP-2-loaded polylactic acid microspheres and nano-hydroxyapatite were added to a gelatin solution; the two solutions were electrospun together using a 10mL syringe, with a flow rate of 0.002mm / s for the PCL solution and 0.0015mm / s for the gelatin mixed solution. The resulting fibers were then vacuum dried for later use.
6. The growth factor gradient biomimetic scaffold according to claim 1, characterized in that, The gelatin adhesive is a 1.0% gelatin aqueous solution prepared by dissolving gelatin in a water bath at 37°C.
7. The method for preparing the growth factor gradient controlled-release scaffold according to claim 1, characterized in that, The preparation materials are non-toxic and safe natural or synthetic polymers, such as gelatin, polylactic acid, and polyvinyl alcohol. The shell material is a synthetic polymer, such as polylactic acid, lactic acid-glycolic acid copolymer, and polycaprolactone, with a molecular weight of 100,000 to 300,000 and a mass concentration of 5% to 20% (w / v). The solvent is one or a mixture of dichloromethane, trichloromethane, trifluoroethanol, hexafluoroisopropanol, and methanol.
8. The growth factor gradient controlled release scaffold according to claim 1, characterized in that, The scaffold can achieve rapid release of CTGF within 14 days, slow release of TGF-β1 within 35 days, and continuous release of BMP-2 in vivo, inducing the proliferation of tendon stem cells and the graded differentiation of mesenchymal stem cells into tendonocytes and osteoblasts.
Citation Information
Cited By
Medical repair membrane with orthogonal limited split structure and preparation method thereof
CN122351597A